Flushing time in Perlas Lagoon and Bluefields Bay, Nicaragua - Brenes, Carlos L. (2007)
The flushing time of Perlas Lagoon and Bluefields Bay were studied in January, March, May, and July 2001. Calculations of the total water volume, tidal prism, mean salinity, and fresh water flows are shown. The flushing times range from 14 to 17 days for Perlas Lagoon and from 2 to 4 days for Bluefields Bay. Flushing time variability, determined largely by the fresh water contribution, is greater for Bluefields Bay, duplicating its magnitude during the dry months compared to the rainy season. In both bodies of water, the relationship between fresh water input and flushing time is inverse: for Bluefields Bay T = 5.2·e-0.0008 (FW), where r2 = 0.835 and for Perlas Lagoon T= 20.2·e-0.0004 (FW), where r2 = 0.873. Key words: flushing time, coastal lagoons, Caribbean Sea.